THE ROLE OF FINANCIAL INCLUSION IN ACHIEVING REQUIREMENTS OF FINANCIAL ENTREPRENEURSHIP FOR GOVERNMENT BANKS - Baneen Mohammed Jawad; Safwan Eldanaoui (Galaxy International Interdisciplinary Research Journal, 2023)
The current study aims to clarify the role of financial inclusion to achieve financial entrepreneurship and analyze the size of the impact to show the relationship between financial inclusion and financial entrepreneurship. The financial inclusion variable has an indirect, statistically significant impact on the financial entrepreneurship variable.), The private banks in Iraq were chosen as a community to apply the current study based on the descriptive analytical approach, and the sample included workers in the studied banks deliberately, as (200) questionnaires were distributed, retrieved Of which (163) questionnaires, and only (160) questionnaires were valid for statistical analysis. The study relied on the program (SPSS.V.26) and the program (AMOS.V.24) with a set of statistical tools such as conducting confirmatory analysis in addition to the simple Pearson correlation to test the correlation between the variables of the study, and structural equation modeling SEM to test hypotheses of influence between the variables studied This study concluded several results, the most important of which are: There is a direct impact of financial inclusion on financial entrepreneurship clearly and at the level of dimensions, and in the light of these results, many recommendations were built, the most important of which are: Paying attention to the variables of the study by educating workers in the study sample banks with (financial inclusion and financial entrepreneurship), and their role in enhancing their ability to provide services distinct from competitors.